Tm-1 back in business: an allele from Solanum pennellii accessions plays a major role in ToBRFV resistance - Romanos Zois; Mireille van Damme; Martin Verbeek; Luuk D. H. Veenendaal; Yuling Bai; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The Tm-1 allele from Solanum pennellii accessions together with an additional, likely recessive, locus are required for complete ToBRFV resistance. Abstract The Tobamovirus Tomato Brown Rugose Fruit Virus (ToBRFV) poses a significant threat to global tomato production. ToBRFV is a mechanically transmitted virus containing a single-stranded positive sense RNA genome. Disease symptoms include brown, rough patches on fruit surfaces, leaf mosaicism and shape abnormalities, and, in advanced stages, total collapse of infected plants. ToBRFV was first detected in the Middle East in 2014 and has rapidly spread to multiple countries across Asia, Europe, and America. In recent years, numerous studies have focused on the identification of ToBRFV resistance traits that are suitable for tomato breeding programs. In this study, we identified five ToBRFV-resistant accessions of Solanum pennellii , a wild relative of cultivated tomato. We confirmed that the major gene controlling this resistance trait is the S. pennellii allele of Tm-1 . Tm-1 was previously identified in S. habrochaites as a semidominant Tomato Mosaic Virus (ToMV) resistance gene. Our results show that full resistance to ToBRFV disease requires an additional undescribed locus. These results show the potential of S. pennellii as a novel source of resistance against ToBRFV.